Mental Health and the COVID-19 Pandemic: Observational Evidence from Malaysia - Tan, Eugenie Sin Sing; Chin, Shaun Ashley Fung Xian; Sathapan, Manimeyapan S. Palaniappan; Dewi, Astrid Disimond; Amini, Farahnaz; Ahmad Bustami, Normina; Tan, Pui Yee; Ho, Yu Bin; Tan, Chung Keat (Multidisciplinary Digital Publishing Institute, 2023)
The interplay of physical, social, and economic factors during the pandemic adversely affected the mental health of healthy people and exacerbated pre-existing mental disorders. This study aimed to determine the impact of the COVID-19 pandemic on the mental health of the general population in Malaysia. A cross-sectional study involving 1246 participants was conducted. A validated questionnaire consisting of the level of knowledge and practice of precautionary behaviors, the Depression, Anxiety, and Stress Scales (DASS), and the World Health Organization Quality of Life—Brief Version (WHOQOL-BREF) was used as an instrument to assess the impacts of the COVID-19 pandemic. Results revealed that most participants possessed a high level of knowledge about COVID-19 and practiced wearing face masks daily as a precautionary measure. The average DASS scores were beyond the mild to moderate cut-off point for all three domains. The present study found that prolonged lockdowns had significantly impacted (p < 0.05), the mental health of the general population in Malaysia, reducing quality of life during the pandemic. Employment status, financial instability, and low annual incomes appeared to be risk factors (p < 0.05) contributing to mental distress, while older age played a protective role (p < 0.05). This is the first large-scale study in Malaysia to assess the impacts of the COVID-19 pandemic on the general population.